PENGARUH SALURAN DISTRIBUSI ONLINE DAN PROMOSI ONLINE TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN PADA CHANDRA SUPERMARKET BANDAR LAMPUNG - Yan Eka Chandra (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2022)
Today the growth of the retail world (retailers) is growing rapidly because basic needs such as food and beverages are present in various types of products available. Since the Covid-19 pandemic emerged, it had an impact on the decline in profits for retail companies in Indonesia. This situation makes purchasing decisions for consumers who are forced to be at home or work from home. This opportunity or opportunity makes online shopping grow rapidly. Chandra Supermarket as one of the offline retail stores has also transformed in distributing online distribution. This company has joined the distribution channel through the Marketplace. The online promotion media carried out are: Website, Facebook, Instagram and TikTok, which are used to promote products sold in supermarkets. So that it can make it easier for consumers to shop from home, easily get products for the various types of retail available. Regular promotions are carried out every week to introduce the products being promoted. Distribution and promotion channels are very influential on purchasing decisions which will result in shopping satisfaction at Chandra Supermarket.